2021
DOI: 10.1021/acs.jpcb.0c08500
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study on the Chemical Absorption Mechanism of CO2 in Diamino Protic Ionic Liquids

Abstract: Diamino protic ionic liquids (DPILs) possess a wide application prospect in the field of acid gas absorption. In this work, two representative DPILs, that is, dimethylethylenediamine 4-fluorophenolate ) and dimethylethylenediamine acetate ([DMEDAH][OAc]), which had been proved to display favorable CO 2 absorption performance in experiments, were selected. Based on the solvation model, the different mechanisms of CO 2 absorption by [DMEDAH] + cations combined with different anions were investigated using the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…From the point of view of physics, Mayer bond order presents the shared electron pairs between two atoms, which can quantitatively reflect the characteristics of chemical bonds and plays an important role in the judgment of chemical bonds. Moreover, Mayer bond order is a physical quantity to judge the strength of chemical bonds; that is, the larger the Mayer bond order, the stronger the bond . The results of the Mayer bond order of dehydrogenation species on the two surfaces are shown in Table and Table S2.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of physics, Mayer bond order presents the shared electron pairs between two atoms, which can quantitatively reflect the characteristics of chemical bonds and plays an important role in the judgment of chemical bonds. Moreover, Mayer bond order is a physical quantity to judge the strength of chemical bonds; that is, the larger the Mayer bond order, the stronger the bond . The results of the Mayer bond order of dehydrogenation species on the two surfaces are shown in Table and Table S2.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, Mayer bond order is a physical quantity to judge the strength of chemical bonds; that is, the larger the Mayer bond order, the stronger the bond. 52 The results of the Mayer bond order of dehydrogenation species on the two surfaces are shown in Table 6 and Table S2. It is seen that Mayer bond order analysis results agree well with those of structural analysis, that is, the average Mayer bond order becomes larger after the whole reaction, and C−C bonds on the whole five-or six-membered ring are enhanced.…”
Section: Adsorption and Co-adsorption Of Dehydrogenated Speciesmentioning
confidence: 99%
“…Based on the high reactivity of phenolate anions for CO 2 capture, Ye and Li et al [ 135 ] reported that the CO 2 absorption capacities of supported dual functionalized phosphonium ILs [aP 4443 ][2-Op] and [aP 4443 ][2-Np] were 1.57 and 1.88 mol CO 2 per mol IL, respectively, via 2:1 mechanism of amino-CO 2 and 1:1 mechanism of phenolate-CO 2 mechanism. Recently, Wang et al [ 136 ] reported two dual-functionalized protic ILs, dimethylethylenediamine 4-fluorophenolate ([DMEDAH][4-F-PhO]) and dimethylethylenediamine acetate ([DMEDAH][OAc]) to investigate the different chemisorption mechanisms via DFT study. Their results showed that, for [DMEDAH][4-F-PhO], phenolate-CO 2 was favorable in kinetics and amino-CO 2 was thermodynamically beneficial; for [DMEDAH][OAc], amino-CO 2 was favorable with proton-transfer to weak acid anion.…”
Section: Functionalized Ils For Co 2 Capturementioning
confidence: 99%
“…Wang and coworkers used density functional theory to construct reaction pathways for CO 2 with diamino protic ionic liquids consisting of a dimethylethylenediamine cation paired with either a 4fluorophenolate or acetate anion. 9 Their calculations suggest that there is a competitive relationship between the anion− cation interaction and the absorption of CO 2 by the anions. Aghaie et al used classical molecular dynamics simulations to study the interactions between water, CO 2 , and the ionic liquid 1-n-butyl-3-methylimidazolium acetate in solution as a function of water concentration.…”
mentioning
confidence: 99%
“…The basicity and size of the anion play key roles in the formation of the phosphonium ylide. Wang and co-workers used density functional theory to construct reaction pathways for CO 2 with diamino protic ionic liquids consisting of a dimethylethylenediamine cation paired with either a 4-fluorophenolate or acetate anion . Their calculations suggest that there is a competitive relationship between the anion–cation interaction and the absorption of CO 2 by the anions.…”
mentioning
confidence: 99%